Cosmic Order and Cultural Astronomy Sacred Cities of India - Singh, Rana P.B. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2009)
Throughout the Indian subcontinent there are territories and areas wherein culture, geography, and the archetypal cosmos interact Other each other to create a sacredscape that is infused Other meaning, cultural performances and transcendent power. These sacred sites possess extensive mythological associations where believed that spirit can cross between different realms. In a broad perspective such studies falls Otherin the realm of cultural astronomy, which has two broad areas, viz. archaeoastr...
Description based upon print version of record.
Keywords: Cities and towns -- Social aspects -- India; India -- Religious life and customs; Sacred space -- India; Sacred space -- India; Cities and towns -- Social aspects -- India; Hindu astronomy; India -- Religious life and customs; RELIGION / Reference; Electronic books